INFLUENCE OF TRUST AND CUSTOMER SATISFACTION ON REPURCHASE INTENTION AT ONLINE SHOP IN THE FACEBOOK - Viajeng Purnama Putri (Manajemen Bisnis, 2015)
The purpose of study was to examine the influence of trust and customer satisfaction on repurchase intention. The sample in this study 100 respondents (Customer Online Shop). The sampling method was purposive sampling method from populations of customer Online Shop in the Facebook. The analysis method was  path analysis. The results of path analysis show that trust and consumer satisfaction influence positive and significant effect on repurchase intention online shop in the Facebook. The trust effect as mediation between consumer satisfaction and repurchase intention.